Pengaruh Penerapan Etika Bisnis Islam, Religiusitas, Dan Kreativitas Terhadap Keuntungan Pengusaha Konfeksi - Devi Faradiska; Rinda Asytuti (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- This study aims to determine the effect of Islamic business ethics and religiosity on the profits of confection entrepreneurs in the village of Pucung Tirto Pekalongan. Methods- Data were collected from 60 respondents using non-probability sampling with convenience sampling techniques. Data were analyzed by multiple linear regression. Findings- The results of the study support the notion that Islamic business ethics and religiosity are two important components that influence the profits of entrepreneurs. Research implications- The results of the study provide empirical evidence that Islamic business ethics and religiosity can be a determinant of an entrepreneur's success.